Pathway from interpersonal sensitivity to depression among Chinese college students during the COVID-19 campus lockdown - Haibo Xu; Yifei Pei; Zheng Yong; Xin Liu; Wei Wang (Komiyama Printing Co. Ltd, 2023)
Background: Due to the continuous spread of the epidemic, some colleges and universities have implemented a campus lockdown management policy in China. In the context of the campus lockdown, this study aimed to explore whether anxiety mediated the association between interpersonal sensitivity and depression, and investigate whether psychological capital moderated the indirect or direct effect of mediation model. Methods: A total of 12945 undergrad students were recruited in China from April 10 to 19, 2022. These participants were asked to complete the online questionnaires measuring interpersonal sensitivity, anxiety, psychological capital, and depression. A moderated mediation model was examined by using PROCESS macro for SPSS 25.0, in which anxiety was a mediating variable, and psychological capital was a moderating variable. Results: Interpersonal sensitivity was positively associated with depression among Chinese college students (r = 0.47, P < 0.001). Anxiety partially mediated the association between interpersonal sensitivity and depression (indirect effect = 2.31, 95%CI [2.18, 2.44], accounting for 70% of the total effect). Moreover, the interaction effect of interpersonal sensitivity and psychological capital on anxiety (β = −0.04, t = −17.36, P < 0.001) and the interaction effect of anxiety and psychological capital on depression (β = 0.002, t = 1.99, P < 0.05) were statistically significant. Conclusions: The current study explained the mediation role of anxiety and the moderation role of psychological capital in the relation between interpersonal sensitivity and depression. The findings suggested that strict monitoring anxiety and promoting psychological capital may decrease the risk of depression among Chinese college students during the campus lockdown.